PENGGUNAAN STRATEGI METAKOGNITIF SISWA DAN PRESTASI BAHASA INGGRIS - Baureh, Gabriella Alleid Dian; Cathrine Sapulete (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the use of metacognitive strategies and the level of students' achievement in English subject. It also seeks to determine whether there is a significant relationship between the use of metacognitive strategies and students' achievement in English. The research employed a quantitative approach with a descriptive-correlational analysis. The study was conducted at SMP Advent UNKLAB and involved over one hundred seventh-grade students selected through convenience sampling. The instruments used for data collection were a questionnaire adapted from the Strategy Inventory for Language Learning (SILL) and the students' English exam results. The findings revealed that students demonstrated a high use of metacognitive strategies and achieved excellent performance in English. Correlation analysis indicated a significant relationship between the use of metacognitive strategies and students' academic achievement. These findings confirm that metacognitive strategies play an important role in supporting students' learning success, particularly in foreign language learning such as English.